Specialized GIS training module: Introduction to GIS, Data and Spatial Analysis, Georeferencing and on-screen digitizing using QGIS - Garcia, Cornelia; Gutierrez, Mary Anne (International Rice Research Institute, 2023)
This GIS training module comprises lectures on the fundamental principles of GIS, complemented by hands-on exercises particularly on on-screen digitizing and georeferencing. At the end of the training, the participants were able to create climate risk maps based on what has been delineated/identified during the CS MAP exercise.